Fabrication and Performances of Flexible Monolithic Dye-sensitized Solar Cell Using Metal Reinforced Porous Counter Electrodes - He, Jiangjing; Wang, Kun; Huang, Fuzhi; Peng, Yong; Cheng, Yi-Bing (Current Nanoscience, 2015)
We report here the world’s first large size plastic monolithic dye-sensitized solar cells (DSCs) with size of 1cmx10cm. A novel printable metal-carbon/graphite composite was used as the counter electrode. By transferring this counter electrode on top of working electrode through a cold isostatic pressing technology, flexible monolithic DSC was successfully fabricated. Our results show that charge transfer resistance of carbon/graphite counter electrode was reduced to about 0.2 Ω.cm2 after being reinforced with magnetron sputtering coated Pt nano particles, which is comparable with sandwich structure plastic DSC with commercial Pt/ITO-PET substrates.
Keywords: metal reinforced carbon/graphite composites